Content and factor validation of the Sieloff-King-Friend Assessment of Group Empowerment within Educational Organizations. (July 2016) - Friend, Mary Louanne; Sieloff, Christina Leibold; Murphy, Shannon; Leeper, James
Abstract: Background and Purpose: Nursing education programs have responsibilities to their stakeholders to prepare graduates who can provide safe, effective patient centered care while leading health care changes. Empowered nurses have been associated with low nurse turnover and higher patient satisfaction; however, less is currently known about group empowerment in nursing education. In order to examine group empowerment in schools of nursing, the Sieloff-King Assessment of Group Empowerment in Organizations (SKAGEO©) was adapted and tested for content validity and confirmatory factor analysis. Methods/Results: The adapted instrument, the Sieloff-King-Friend Assessment of Group Empowerment within Educational Organizations (SKFAGEEO) was first reviewed by nurse experts who provided quantitative and qualitative data regarding each item. A total of 320 nurse deans and faculty comprised the final sample for the second order confirmatory 8 factor analysis. Findings revealed factor loadings ranging from .455 to .960.The overall fit of the propose model was Chi Square = 1383. 24, df = 566, p < .001; GFI = .786, RMSEA = 0.69. Conclusions: The study results indicated that the SKFAGEEO has acceptable psychometric properties. Highlights: The Sieloff King Assessment of Group Empowerment within Organizations (SKAGEO) was adapted for use in educational environments. Content and confirmatory factor analyses support the use of the instrument in a sample of 320 deans and faculty in American Association College of Nursing (AACN) member schools. The overall fit of the model was χ 2 (566, N = 320) = 1383. 24, p < .001; GFI =. 786, RMSEA = 0.69 indicating an acceptable fit with the data.